Gut microbial metabolite p-cresol alters biotransformation of bisphenol A: enzyme competition or gene induction? - Peng, Bo (2022)
Recent studies on pharmaceuticals have revealed the direct and indirect mechanisms that link human gut microbiome to xenobiotic biotransformation. Though environmental contaminants compose a vital portion of xenobiotics and share overlapping biotransformation pathways with gut microbial metabolites, the possible interplay between gut microbiome and biotransformation of environmental contaminants remains obscure. This study utilized bisphenol A (BPA) and p-cresol as model compounds to explore whether gut microbial metabolites could affect environmental phenol metabolism on both in vitro and in vivo models. We have observed some distinct biotransformation behavior, where in vivo mouse examination using 171 & 1972 μg/kg bw p-cresol injection exhibited enhancing effect on BPA metabolism, but p-cresol was found as a strong inhibitor from 10/5 μM in a non-competitive pattern for BPA biotransformation in in vitro models of liver S9 fractions and HepG2 cell line, respectively. A further investigation revealed that the expression of biotransformation enzyme genes including Ugt1a1, Ugt2b1, or Sult1a1 of p-cresol treated mice were dynamically induced. In silico docking approach was also utilized to explore the non-competitive inhibition mechanism by estimating the binding affinity of key enzyme SULT 1A1. Overall, our results provided a novel insight into the biotransformation interaction between gut microbiome and environmental contaminants.